Symposium 13: Impact of prediabetes on microvascular disease - María Florencia Aranguren (Revista de la Sociedad Argentina de Diabetes, 2022)
Many studies have reported that more than a third of adults newly diagnosed with type 2 diabetes have some degree of renal, retinal, or neuropathic damage from the onset of the disease, suggesting that the alterations that lead to microvascular disease begin early.